Cinética do desenvolvimento de alterações no perfil inflamatório, função endotelial e cardiovascular na obesidade experimental - Oishi, Jorge Camargo (2016)
Obesity is a metabolic disorder and its prevalence is increasing worldwide, which in turn significantly increase the morbidity and mortality rates associated. Obesity is associated with several diseases risk factors, the expand of adipose tissue lead a chronic inflammatory state, insulin resistance, endothelial dysfunction and hypertension and cardiovascular diseases. The hallmark of obesity is the low grade inflammation, with increase of production and secretion of several proinflammatory cytokines that lead to insulin resistance and endothelial dysfunction, which is a precursor to cardiovascular disease and cardiovascular outcome. Therefore, the aim of this study was to investigate the evolution of comorbidities together with obesity evolution. In this way, we fed Wistar male rats with a palatable high fat diet during twenty-four weeks and every 6 weeks was evaluate: The inflammatory state by measuring cytokines pro-inflammatory (interleukin -6 tumor necrosis factor –α, reactive C protein) and anti-inflammatory adiponectin; the endothelial function; the Nitric Oxide levels, blood pressure and cardiac contractile. Our results indicated that six weeks of high fat feeding rats increase visceral fat and triggers inflammatory state, insulin resistance and endothelial dysfunction. At 12 weeks of high fat diet an increase in blood pressure and lipid peroxidation in aorta was observed and at 24 weeks an impaired on cardiac contractile was observed. To our knowledge, this is the first study showing the evolution of metabolic disorders in high-fat diet model.